FUS Selectively Facilitates circRNAs Packing into Small Extracellular Vesicles within Hypoxia Neuron - Jiankun Zang; Yousheng Wu; Xuanlin Su; Kaiwei Cai; Man Ke; Niu He; Huili Zhu; Zefeng Tan; Jielin Zhu; Wensheng He; Min Peng; Shiqing Zhang; et al. (Advanced Science, 2025)
Abstract Small extracellular vesicles (sEVs) contain abundant circular RNAs (circRNAs) and are involved in cellular processes, particularly hypoxia. However, the process that packaging of circRNAs into neuronal sEVs under hypoxia is unclear. This study revealed the spatial mechanism of the Fused in Sarcoma protein (FUS) that facilitates the loading of functional circRNAs into sEVs in hypoxia neurons. It is found that FUS translocated from the nucleus to the cytoplasm and is more enriched in hypoxic neuronal sEVs than in normal sEVs. Cytoplasmic FUS formed aggregates with the sEVs marker protein CD63 in cytoplasmic stress granules (SGs) under hypoxic stress. Meanwhile, cytoplasmic FUS recruited of functional cytoplasmic circRNAs to SGs. Upon relief of hypoxic stress and degradation of SGs, cytoplasmic FUS is transported with those circRNAs from SGs to sEVs. Validation of FUS knockout dramatically reduced the recruitment of circRNAs from SGs and led to low circRNA loading in sEVs, which is also confirmed by the accumulation of circRNAs in the cytoplasm. Furthermore, it is showed that the FUS Zf_RanBP domain regulates the transport of circRNAs to sEVs by interacting with hypoxic circRNAs in SGs. Overall, these findings have revealed a FUS‐mediated transport mechanism of hypoxia‐related cytoplasmic circRNAs loaded into sEVs under hypoxic conditions.